2019
DOI: 10.1007/s40142-019-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges of Rare Genetic Variation in Alzheimer’s Disease

Abstract: Purpose of Review It is well established that sporadic Alzheimer's disease (AD) is polygenic with common and rare genetic variation alongside environmental factors contributing to disease. Here, we review our current understanding of the genetic architecture of disease, paying specific attention to rare susceptibility variants, and explore some of the limitations in rare variant detection and analysis. Recent Findings Rare variation has been shown to robustly associate with disease. These include potentially d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…While this is relatively straightforward when performing GWAS using data from genotyping arrays, it is more complex when merging data generated using different exome capture methods and with varying coverage [ 89 ]. Sequence capture uniformity and capture probe performance will determine how much raw sequence data for each sample will be available and, consequently, impact downstream analyses [ 90 ].…”
Section: The Challenges When Studying Rare Variantsmentioning
confidence: 99%
“…While this is relatively straightforward when performing GWAS using data from genotyping arrays, it is more complex when merging data generated using different exome capture methods and with varying coverage [ 89 ]. Sequence capture uniformity and capture probe performance will determine how much raw sequence data for each sample will be available and, consequently, impact downstream analyses [ 90 ].…”
Section: The Challenges When Studying Rare Variantsmentioning
confidence: 99%
“…Recent large scale studies of AD genetics, employing genome-wide association studies (GWAS), whole exome sequencing (WES), and whole genome sequencing (WGS), have defined additional genes whose variants contribute to increased risk [ 53 , 54 ]. These include Clusterin (CLU), Sortilin-related receptor-1 (SORL1), ATP-binding cassette subfamily A member 7 (ABCA7), Bridging integrator 1 (BIN1), phosphatidylinositol binding clathrin assembly protein (PICALM), CD2 associated protein (CD2AP), Complement component (3b/4b) receptor 1 (CR1), CD33, triggering receptor expressed on myeloid cells 2 (TREM2), and phospholipase D3 (PLD3) [ 55 , 56 , 57 ]. Intriguingly, more than 50% of validated gene variants are implicated in innate immune and microglial functions [ 58 , 59 , 60 ], including the top two AD risk genes, APOE and TREM2 [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also found a contribution of rare variants in genes such as TREM2 and ABCA7 toward AD [ 3 5 ]. A popular approach to discover AD relevant rare variants is the use of whole-exome/genome sequencing to assess rare-variants globally, and then to associate each variant with AD status [ 6 ]. However, the occurrence of AD is caused by a combination of pathways involving inflammation, cholesterol metabolism, tau pathology, endosome or ubiquitin-related functioning [ 7 ].…”
Section: Introductionmentioning
confidence: 99%